ChemInform Abstract: Unexpected Nitrilimine Cycloaddition of Thiazolo[3, 2‐a]pyrimidine Derivatives. Issue 16 (22nd April 2014) - Liu, Bin; Li, Xiao‐Fang; Liu, Hao‐Chong; Yu, Xian‐Yong
Abstract The 1, 3‐dipolar cycloaddition of the in situ generated diphenylnitrilimine to substrate (I) proceeds regio‐ and site‐selectively.